Influence of the Hydrocarbon Chain Length of Alkylammonium Chlorides on Their Adsorption by Flotation Carriers - E.A. Streltsova; L.D. Skrylev; A.F. Tymchuk; E.A. Hromysheva (Adsorption Science & Technology)
Alkylammonium chlorides whose adsorption/micelle energetic ratio (AMER) is close to unity are those adsorbed most effectively on the surface of a solid carrier (adsorbent). A change in the solution pH leads to a change in the hydrocarbon chain length of the alkylammonium chlorides with AMER values close to unity and hence to a positive change on the length of the hydrocarbon chain adsorbed on the carrier surface.